Silicon (100) surfaces modified by osmium bipyridine complexes - Ciampi, Simone; Lai, L.; Gooding, J. (2010)
Tethered osmium bypiridine-pyridine complexes [Os(bpy)2Clpy-R] were prepared from chemically modified non-oxidized silicon (100) electrodes. Pyridinyl groups at the distal end of self-assembled monolayers (SAMs)-modified silicon surfaces were used to coordinatively bind a representative osmium bipyridil complex precursor [Os(bpy)2Cl2]. SAMs presenting the putative osmium ligand were prepared by a step-wise procedure using click reactions of acetylene-terminated alkyl monolayers and isonicotinic acid azide derivatives. The redox properties of the modified Si(100) electrodes were characterized using cyclic voltammetry. © 2010 IEEE.